The application of temperature sensors into fabric substrates. - Jones, Alexander R. (Kansas State University, 2011)
With continuing advancements in the area of electronics, there are more ways in which they are utilized in order to improve the lives of humans. These advancements have to led to the incorporation of electronic components into fabric structures, creating electronic textiles (e-textiles). As it has become possible to place small electrical components within clothing without the performance of the electronics being hampered, research has been conducted in the use of e-textiles in measuring aspects of the human body, such as the heart rate and perspiration rate. In the area of skin temperature, research has been conducted in the past using e-textiles for skin temperature measurement, but past efforts have been unsuccessful in incorporating useable temperature sensors into a fabric substrate. This study compared three types of sensors incorporated into woven and knitted fabrics, using insulated thermocouples, un-insulated thermocouples, and resistance temperature directors (RTDs). Three incorporation methods (weaving, interlacing into knit, and stitching) were used in six fabric samples, with the three sensor types woven and stitched into three woven fabric samples, while the sensors were interlaced into knitted fabric and stitched into the three knitted samples. Fabric hand washing and temperature measurement tests were conducted, and the temperature readings were analyzed statistically for comparison. The analysis conducted showed that the thermocouples that were interlaced or stitched onto the knitted fabric samples were best for temperature measurement due to their accuracy and durability, while the RTDs were unusable as a temperature sensor, as the removal of the electrical connectors during washing eliminated the calibration that was established before washing. This research was supported in part by the Institute for Environmental Research at Kansas State University.
Keywords: Electronic textiles; Textile Research (0994)